Sistem Informasi Inventory Barang Berbasis Web Pada Apotek Afifah Farma Dengan Metode Waterfall - Syahlan Sugiarto; Muhtajuddin Danny (Prosiding Sains dan Teknologi, 2022)
The information systems are systems that process and provide information for decision-making in an organization. Inventory information system is a system used to process and provide information about inventory data in a company for decision making. Goods Inventory Information System at Apotek Afifah Farma still uses a manual process. The purpose of this research is to develop an ongoing inventory information system at Apotek Afifah Farma to support warehouse-based inventory of warehouse stock. The methodology used to develop the inventory information system of this item is the waterfall method and uses the PHP and MySQL. Keywords: Informatika System, Inventory, PHP, MySql